Pre-extensively drug-resistant and extensively drug-resistant tuberculosis in Latin America and the Caribbean: A systematic review and meta-analysis - Alarcon-Braga, Esteban A. (2024)
Background: The growing threat from pre-extensively drug-resistant tuberculosis (pre-XDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) poses a major public health concern in Latin America and the Caribbean (LAC). Therefore, this study aimed to summarize the available evidence on the prevalence of pre-XDR-TB and XDR-TB among patients with multidrug-resistant tuberculosis in LAC. Methods: A systematic review was conducted in the following databases on June 3, 2023: PubMed, Scopus, Ovid Medline, Web of Science, Scielo and LILACS. We estimated pooled proportions using a random effects model (Dersimonian and Laird). The 95% confidence intervals (95% CI) were calculated using the binomial exact method (Clopper-Pearson Method). Subgroup (by time period and country) and sensitivity analyses were performed. Results: Twenty-nine studies were eligible for qualitative synthesis and 27 for meta-analysis (n = 15,565). The pooled prevalence of XDR-TB in the study participants was 5% (95% CI: 3%-6%), while that of pre-XDR-TB was 10% (95% CI 7%-14%). Cuba (6%, 95% CI 0%-17%) and Peru (6%, 95% CI 5%-7%) had the highest pooled prevalence of XDR-TB. Regarding pre-XDR-TB, Brazil (16%, 95% CI 11%-22%) and Peru (13%, 95% CI: 9%-16%) showed the highest prevalence. Conclusions: The pooled prevalence of pre-XDR-TB and XDR-TB in LAC was 10% and 5%, respectively. Governments should strengthen drug-resistance surveillance and TB programs.